Entirely Biomass-Derived Hydrogel Composites for Possible Applications in Drug Delivery - Fitzgerald, Megan M.; Morgan, Melissa A.; Kerton, Francesca M. (Sustainability & Circularity NOW, 2025)
Entirely biomass-based chitosan-alginate hydrogel composites were prepared using mussel-derived calcite. Composite hydrogel beads were prepared with 0.0, 1.0, and 2.5 wt % calcite and were characterized using IR spectroscopy, scanning electron microscopy (SEM), and thermogravimetric analysis (TGA). Diameters of beads were measured to ensure uniform preparation. The swelling behavior of beads was tested in 0.1 M HCl, 0.1 M potassium phosphate buffer, and deionized water at 37 °C. Beads containing calcite were found to have significantly less swelling ability in 0.1 M HCl and deionized water, but in 0.1 M potassium phosphate buffer, no change in swelling ability was observed for beads containing zero calcite compared with those containing calcite. Encapsulation efficiency (EE) measurements of methylene blue, as a model drug, showed that 0.0 wt % calcite beads had an EE of 80.8% and those containing calcite had lower EE: 60.7% (1.0 wt % calcite) and 71.6% (2.5 wt % calcite). Methylene blue release in a surrogate gastric environment (0.1 M HCl followed by 0.1 K buffer) showed that 0.0 wt % calcite beads had the least controlled release, whereas those containing calcite showed controlled release. Drug release results were found to be significant through a one-way ANOVA test (p < 0.05). TGA data show that SC levels in beads after placement in a surrogate gastric fluid (0.1 M HCl) are significantly reduced due to the reaction between calcite and HCl.
Keywords: Biomaterials; Renewable; Calcium carbonate; Blue economy; Biomass; Polysaccharides; Drug release